PELAKSANAAN LAYANAN INFORMASI DALAM MERUBAH PERILAKU MORAL PESERTA DIDIK OLEH GURU BK DI KELAS VIII SMP NEGERI 1 PAINAN - Yanti, Meli Fitri (Bimbingan dan Konseling, 2014)
This research of background by the implementation of information services on moral behavior. The purpose of this research is to describe; 1) the Implementation of information services in changing moral behavior of learners by counselor related to planning. 2) implementation. This research is descriptive of quantitative. The population of all the students of class VIII 211 people. Sampling was done using simple random sampling technique. This research took a sample of students who serve as the primary respondents totaling 68 people. The instrument used in this study was a questionnaire. As for the used of data analysis techniques percentage. The results of of this research revealed that: 1) The of information services in the changing moral behavior of learners by teachers BK related to planning was at a very good category. 2) the Implementation of information services in changing moral behavior of learners by teachers associated with the implementation of the BK was in the good category.